STATUS OF THE INDONESIAN OIL AND GAS BLOCKS ON BORDERS WITH NEIGHBORING COUNTRIES - Djoko Sunarjanto; Susilohadi Susilohadi; Suliantara Suliantara; Abdul Gaffar (Scientific Contributions Oil and Gas, 2016)
Although revenue from the oil and gas industry is no longer the main source of national income, it is still playing a strategic role. The oil and gas industry is known as a high-tech, a high-risk, and a high-capital industry, on which the country has limited capacity for regional development, especially of the resources in areas located along the national border. The main objective of this research is to closely identify the recent growth centre status of blocks and sedimentary basins located along the national border. The study relies on published reports, studies, and data such as bathymetry map, national geographic and jurisdiction map, and maps of existing oil and gas blocks. All data were managed under a geographic information system application in order to conduct comparative and qualitative analysis of those overlaying data. Some oil and gas blocks that are located near to neighboring countries, such as Singapore, Malaysia, Brunei, Vietnam, The Philippines, Papua New Guinea, East Timor, and Australia have been categorized based on these methods of scoring and ranking analysis to identify new economic centres of growth. Three categories are suggested: very important, important, and ordinary as new growth centres. The Natuna Sea blocks, Iwur, and Timor blocks are considered to be important.